Advancing Circular Economy and Competitiveness through Green Supply Chain Management in Plastic Recycling Industry - Purwanto, Setiyo; Perkasa, Didin Hikmah; Ali, Muhammad (Universitas Medan Area, 2024)
This research investigates the influence of product competitiveness (PC) and green supply chain mana-gement (GSCM) on firm performance (FP) in Indonesia's plastic recycling industry, with a particular emphasis on the mediating role of import regulation (IP). Furthermore, it evaluates the moderating effect of top management commitment (TMC) on the relationship between GSCM and PC, as well as between PC and FP. Data were collected through questionnaires administered to employees and business stake-holders within the plastic supply chain and subsequently analyzed using PLS-SEM via SmartPLS. Hypotheses were formulated to explore the interactions among PC, GSCM, IP, TMC, and FP within a circular economy framework. The findings indicate that government import regulations significantly enhance PC and FP. Moreover, TMC strengthens the efficacy of GSCM, resulting in improved FP. The study highlights the environmental and economic benefits of the circular economy, particularly its potential to reduce dependence on imported virgin plastic in Indonesia. These results underscore the critical role of regulatory support and management commitment in advancing sustainable practices within the plastic recycling sector.